1987
DOI: 10.1002/1097-0142(19870101)59:1<184::aid-cncr2820590135>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Cancer among haitians in Florida

Abstract: Data on cancer rates from West Indian populations are scarce, and to the authors' knowledge there are no published data on cancer rates and distributions among Haitians. Proportional distributions of cancers among three groups of patients living in Florida were compared: Haitian born blacks, United States born blacks, and non-Haitian Caribbean born blacks. The incidence rate of cancer of the cervix among the Haitian and United States born black groups was also compared. Increased rates of certain malignancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, while researchers have historically ignored immigrant subpopulations of African-and Caribbean-American women in the United States (27)(28)(29)(30)(31), our data suggest that this process must not be allowed to continue. When operationalized precisely, there were significant differences across six ethnic groups.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, while researchers have historically ignored immigrant subpopulations of African-and Caribbean-American women in the United States (27)(28)(29)(30)(31), our data suggest that this process must not be allowed to continue. When operationalized precisely, there were significant differences across six ethnic groups.…”
Section: Discussionmentioning
confidence: 73%
“…Complicating this picture is the fact that, although BMI differences between women of European and African descent are well documented (24,25), there is virtually no descriptive information regarding the body mass characteristics of subpopulations of African‐ and Caribbean‐American women in the United States. Few studies have included sufficient numbers of African‐American women (26), much less considered the uniqueness of Caribbean subpopulations (27). Instead, minority women are subsumed within the “black” and “Hispanic” rubrics (28,29), the implicit assumption being that there is no variation in risk factors within these groups.…”
Section: Introductionmentioning
confidence: 99%
“…A high rate of cervical neoplasia in Haitians has also been reported from Miami. 10 The finding of an average incidence of breast cancer among US-born Black women in Brooklyn underlines the value of examining ethnic differences, since the overall rate in Black women would otherwise appear encouragingly low. The below-average incidence ofbreast cancer in both Haitian and English-speaking Caribbean immigrants is consistent with other studies which show persistently low rates ofbreast cancer in migrants from countries with low incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Further research will be needed to better characterize any possible interaction of age and ethnicity with respect to Pap smear acquisition. The higher incidence of invasive cervical cancer in Haitian immigrant women 5,6,25,43 has been attributed to lower rates of Pap smear acquisition in this community. However, in the present study, the initially observed relationship of ethnicity to receipt of Pap smears was explained by health care delivery variables and specific demographic characteristics.…”
Section: ϭ Confidence Intervalmentioning
confidence: 99%
“…[1][2][3][4] These findings may be due to later detection of cervical cancer in minority women. A retrospective review of data from a tumor registry 5 and data from a case series 6 suggest that the burden of cervical cancer is higher in the Haitian immigrant community than in other communities of color. There is some evidence of lower Pap smear rates among women who selfidentified as Haitian than among other women of color in New York City; 7 however, little direct research has been done on cervical cancer in the Haitian immigrant community.…”
mentioning
confidence: 99%